94.7k views
2 votes
Helppppppppp please

Helppppppppp please-example-1

1 Answer

6 votes

Answer:

A, C

Explanation:

Quadratic formula:


x = \frac{ - b± \sqrt{b^(2) - 4ac } }{2a}

a is the coefficient of x², b is the coefficient of x and c is the constant when a second degree polynomial is equal to zero. (ax² +bx +c= 0)

x² +5x +11= 0

a= 1, b= 5, c=11

Thus, using the quadratic formula:


x = \frac{ - 5± \sqrt{ {5}^(2) - 4(1)(11)} }{2(1)} \\ x = ( - 5± √(25 - 44) )/(2) \\ x = ( - 5± √( - 19) )/(2)

∴The answers are A and C.

User Niemah
by
5.7k points